Public Views of Dairy Calf Welfare and Dairy Consumption Habits of American Youth and Adults - Perttu, Rielle K.; Ventura, Beth A.; Rendahl, Aaron K.; Endres, Marcia I. (Frontiers in Veterinary Science, 2021)
The primary objective of this study was to explore views of dairy calf welfare and dairy product consumption habits among youth and adults. The secondary objective was to explore views of dairy calf welfare and dairy product consumption habits among a subset of parent-child pairs. Participants 5–17 years of age (n = 463) and 18 years old or greater (n = 1,310) completed an in-person survey at the Minnesota State Fair (St. Paul, MN, USA) in summer 2018. A subset of these data was comprised of parent-child pairs (n = 188). The survey was administered via Qualtrics using iPads and included multiple-choice questions about demographics and calf welfare, an open-ended question on “what dairy calves need to have a good life,” and multiple-choice questions about participants' consumption of dairy products and nondairy alternative products. Content analysis was used for responses to the open-ended question, and concepts to describe dairy calf welfare views were identified. Fisher's exact test and Cohen's Kappa were used to investigate the relationships between parent-child pair responses about dairy calf welfare. In addition to these methods, prevalence-adjusted and bias-adjusted kappa (PABAK) were used to investigate the relationships between parent-child pair responses about consumption habits. The median age of all youth participants was 11 years and 61% were female, 82% were urban residents, and 63% did not have prior experience handling agricultural animals but 83% had visited a farm in the past. Most youth participants (94.4%) indicated that they consumed dairy products, while 47.1% consumed nondairy alternatives products. Median age range of all adult participants was 45–54 years, 65% were female, 82% urban residents, and 81% did not have prior experience handling agricultural animals but 63% had visited a farm in the past. Most adult participants (94%) indicated that they consumed dairy products and 47% indicated that they consumed nondairy alternative products. In response to “what dairy calves need to have a good life,” youth and adults most commonly focused on issues related to biological functioning (82 and 70% of youth and adults mentioning this concept, respectively), followed by natural living (44 and 50%, respectively), humane care (30 and 20%, respectively), and affective states (5% of both youth and adults). For the natural living concept of animal welfare, parent and child responses were slightly associated (Kappa = 0.19; P = 0.01; overall agreement = 61%). Almost all participants reported consuming dairy products, therefore, the agreement is high between parents and children because in most households (90%), both parents and children consume dairy products. However, child consumption was observed to be lower (75%, 9/12) when parents do not consume dairy than when parents do consume dairy (95%, 167/176), leading to a Kappa of 0.20 (P = 0.006, PABAK = 0.81) and a slight association between parents and children. The results suggest that biological functioning is highly valued by the public and views of parents and their children related to natural living in dairy calves are slightly associated.